(untitled) (American Journal of Islam and Society, 2013)
Both a book of lamentation about the presumably collapsing American way of life and a populist right-wing anti-establishment agenda of ethno-nationalist xenophobia, euphemistically referred to as “ethno-pluralism,” author Patrick Buchanan presents an alarmist message of doom and gloom about the fate of his country. He adopts this “master frame,” which allows him and the current he represents to mobilize anti-immigrant sentiments as well as political protest in ways that limit vulnerabilities to accusations of racism or of being antidemocratic (Rydgren 2004).1 Buchanan starts his book by asserting that this generation of Americans is witnessing “one of the most stunning declines of a great power in the history of the world” (p. 10). His thesis is that “America is disintegrating” and that the “centrifugal forces pulling [it] apart are growing inexorably. What once united us is dissolving. And this is true of Western civilization” (p. 7; my emphasis). The explanation he offers for this is framed within the context of the United States losing its Christian character, implying that non-Christians do not belong there; the breakdown of society’s moral, cultural, and social fabric, read as opposition to multiculturalism as well as to liberal values and policies; and the dying of the people who created this nation, which is now being overwhelmed by a rapidly increasing flow of immigrants and members of other races and ethnicities. Having rung the alarm, whether true or false, Buchanan proceeds in the following eleven chapters to make his case, addressing sensitive issues of religion, race and ethnicity, demography, multiculturalism, expansive government, values of equality, and foreign relations – all of which he has something to say about in what appears to be some kind of an ideological tract ...